Ubiquitous expression of the Pik3caH1047R mutation promotes hypoglycemia, hypoinsulinemia, and organomegaly. Issue 4 (30th December 2014) - Kinross, Kathryn M.; Montgomery, Karen G.; Mangiafico, Salvatore P.; Hare, Lauren M.; Kleinschmidt, Margarete; Bywater, Megan J.; Poulton, Ingrid J.; Vrahnas, Christina; Henneicke, Holger; Malaterre, Jordane; Waring, Paul M.; Cullinane, Carleen; et al.
Abstract : Mutations in PIK3CA, the gene encoding the p110α catalytic subunit of PI3K, are among the most common mutations found in human cancer and have also recently been implicated in a range of overgrowth syndromes in humans. We have used a novel inducible "exonswitch" approach to knock in the constitutively active Pik3ca H1047R mutation into the endogenous Pik3ca gene of the mouse. Ubiquitous expression of the Pik3ca H1047R mutation throughout the body resulted in a dramatic increase in body weight within 3 weeks of induction (mutant 150 ± 5%; wild‐type 117 ± 3%, mean ± sem ), which was associated with increased organ size rather than adiposity. Severe metabolic effects, including a reduction in blood glucose levels to 59 ± 4% of baseline (11 days postinduction) and undetectable insulin levels, were also observed. Pik3ca H1047R mutant mice died earlier (median survival 46.5 d post‐mutation induction) than wild‐type control mice (100% survival > 250 days). Although deletion of Akt2 increased median survival by 44%, neither organ overgrowth, nor hypoglycemia were rescued, indicating that both the growth and metabolic functions of constitutive PI3K activity can be Akt2 independent. This mouse model demonstrates the critical role of PI3K in the regulation of both organ size and glucose metabolism at the whole animal level.—Kinross, K. M., Montgomery, K. G., Mangiafico, S. P., Hare, L. M., Kleinschmidt, M., Bywater, M. J., Poulton, I. J., Vrahnas, C., Henneicke, H., Malaterre, J., Waring, P. M., Cullinane, C., Sims, N. A., McArthur, G. A., Andrikopoulos, S., Phillips, W. A. Ubiquitous expression of the Pik3ca H1047R mutation promotes hypoglycemia, hypoinsulinemia, and organomegaly. FASEB J. 29, 1426‐1434 (2015). www.fasebj.org